Perlindungan Hukum Anak Dari Perkawinan Campuran Yang Tinggal di Indonesia (LEGAL DIALOGICA, 2025)
This research aims to understand the status of children born from mixed marriages according to Law Number 1 of 1974 concerning Marriage and to identify and analyze the legal protection for children in relation to civil rights resulting from mixed marriages according to Law Number 1 of 1974 concerning Marriage and Law Number 12 of 2006 concerning Citizenship. This study falls into the category of normative legal research, which uses a literature-based approach to various legal materials. This study focuses on law as a system of norms, so the main analysis is directed at examining the applicable regulations.The results of this research indicate that the status of children born from mixed marriages according to Law No. 1 of 1974 concerning Marriage, has legal status and civil rights that are protected. However, in practice, this protection has not been optimal due to administrative obstacles and a lack of socialization that hinders children's access to legal status and their rights. Legal protection for children resulting from mixed marriages according to Law No. 1 of 1974 and Law No. 12 of 2006 guarantees the legal status of children and their civil rights, including the right to maintenance, education, and citizenship. However, in practice, its implementation has not been optimal due to persistent administrative barriers and weak coordination among related agencies.The author's recommendation in this research is that the government needs to simplify administrative procedures, improve legal socialization to the community, especially through the Ministry of Law and Human Rights, the Ministry of Home Affairs, and the Population and Civil Registration Office. It is also necessary to formulate clearer and more integrated technical regulations regarding the legal status of children born from mixed marriages. In addition, legal aid services and special assistance need to be provided by Legal Aid Institutions (LBH).Abstrak:Penelitian ini bertujuan Untuk Memahamai dari status anak yang lahir dari perkawinan campuran menurut Undang-Undang Nomor 1 Tahun 1974 tentang Perkawinan dan Untuk mengetahui dan menganalisis perlindungan hukum bagi anak dalam kaitannya hak-hak keperdataan hasil dari perkawinan campuran menurut Undang-Undang Nomor 1 Tahun 1974 tentang Perkawinan dan Undang-Undang Nomor 12 Tahun 2006 tentang Kewarganegaraan. Penelitian ini termasuk dalam jenis penelitian hukum normatif, yang menggunakan pendekatan berbasis studi kepustakaan terhadap berbagai bahan hukum. Kajian ini memusatkan perhatian pada hukum sebagai suatu sistem norma, sehingga analisis utama diarahkan pada penelaahan terhadap aturan yang berlaku.Hasil penelitian ini mengindikasikan bahwa Status anak yang lahir dari perkawinan campuran menurut Undang-Undang Nomor 1 Tahun 1974 tentang Perkawinan, memiliki status hukum yang sah dan hak-hak keperdataan yang dilindungi. Namun, dalam praktiknya, perlindungan tersebut belum maksimal karena masih terdapat kendala administratif dan kurangnya sosialisasi yang menghambat akses anak terhadap status hukum dan hak-haknya dan Perlindungan hukum bagi anak hasil perkawinan campuran menurut Undang-Undang No. 1 Tahun 1974 tentang Perkawinan dan Undang-Undang No. 12 Tahun 2006 tentang Kewarganegaraan  menjamin status sah anak serta hak-hak keperdataannya, termasuk hak atas pemeliharaan, pendidikan, dan kewarganegaraan. Namun, secara praktik, pelaksanaannya belum maksimal karena masih terdapat hambatan administratif dan lemahnya koordinasi antarinstansi terkait.Rekomendasi penulis pada penelitian ini Pemerintah perlu menyederhanakan prosedur administrasi, meningkatkan sosialisasi hukum kepada masyarakat, khususnya melalui Kementerian Hukum dan HAM, Kementerian Dalam Negeri, serta Dinas Kependudukan dan Catatan Sipil, perlu menyusun regulasi teknis yang lebih jelas dan terpadu terkait status hukum anak hasil perkawinan campuran. Selain itu, perlu disediakan layanan bantuan hukum dan pendampingan khusus oleh Lembaga Bantuan Hukum (LBH).